Urban rent generation: The esenkent case in Istanbul - Aysegul Yakar-Onal (European Regional Science Association (ERSA), 2001)
An increasing proportion of the rapidly growing world population is attempting to satisfy its economic and social needs in an urban context. The migration of people into cities results in urban growth. As a result of this process of urban growth, there is an increasing demand for urban land. Within urban areas land use is subject to fewer changes. Because instant increase in the supply of land in central areas is impossible, there is an increase in the spatial extent of the central area through an invasion of the surrounding zone. Therefore, there is a need to transform non-urban areas to urban areas. This transformation generates urban rents in those newly created urban areas and also re-forms all urban rents in the city. Considering the pace of urbanization in Turkey, it is seen that most of the largest cities are continuing to grow very rapidly. Istanbul is the largest city in Turkey and a population growth continues in Istanbul because of the immigration. Therefore Istanbul is growing in terms of population and also in terms of urban sprawl. In this research, as a good example of the urban sprawl in Istanbul a residential area, which is called Esenkent, will be examined in the context of the generation of rent. As an example, Esenkent is important because the land on which Esenkent is established was expropriated by the local municipality. Therefore, there is a public intervention on urban rents. It means that the structure of property on land was changed. Briefly, urban rent generation in the residential area called Esenkent will be examined on the basis of private property rights and the price changes of properties. Our analysis will depend on the data from official land registers, real estate advertisements on newspapers and the interviews with the real estate agents.
Keywords: 330